Research of the conceptual principles of pharmaceutical industry sustainable development formation - Moroz, Svitlana; Sahaidak-Nikityuk, Rita; Zoidze, Diana (ScienceRise: Pharmaceutical Science, 2017)
The analysis of the current state of the pharmaceutical industry of the country indicates its poor ability to meet the requirements in medicines for people by criteria defined by the National Drug (Pharmaceutical) Policy: accessibility, quality and rational use of medicines, and consequently – the inability to provide the nation’s health potential and work ability. In this context, there is a necessity for more balanced and focused strategic development of the branch, in particular – based on the sustainable development paradigm. Aim. The aim of research was to define the concept of the sustainable development and its importance for pharmaceutical industry of Ukraine. Methods. System approach, the historical method, comparison and synthesis were used in the study. Results. Review of the main approaches to the interpretation of the concepts of "development", "movement", "sustainability", and their correlation was carried out. It was determined that the sustainable development provides balance, quality change, expansion and potential opportunities realization. The necessity of Ukrainian pharmaceutical industry development as part of sustainable development philosophy and concept was substantiated. Conclusion. Determination of the sustainable development in pharmacy, in which, based on the general stability principles, the National Drug Policy strategic objectives and common mechanism to ensure such development were considered, was displayed